Cognitive Training for Mild Traumatic Brain Injury and Posttraumatic Stress Disorder - Samuelson, Kristin W.; Engle, Krista; Abadjian, Linda; Jordan, Joshua; Bartel, Alisa; Talbot, Margaret; Powers, Tyler; Bryan, Lori; Benight, Charles (Frontiers in Neurology, 2020)
Although there is evidence of mild cognitive impairments for many individuals with mild traumatic brain injury (mTBI) and posttraumatic stress disorder (PTSD), little research evaluating the effectiveness of cognitive training interventions has been conducted. This randomized controlled trial examined the effectiveness of a 9-hour group cognitive training targeting higher-order functions, Strategic Memory Advanced Reasoning Training (SMART), compared to a 9-hour psychoeducational control group in improving neurocognitive functioning in adults with mTBI and PTSD. A sample of 124 adults with histories of mild TBI (n = 117) and/or current diagnoses of PTSD (n = 84) were randomized into SMART (n = 66) or Brain Health Workshop (BHW; n =58) and assessed at three time points: baseline, following training, and six months later. Participants completed a battery of neurocognitive tests, including a test of gist reasoning (a function directly targeted by SMART) as well as tests of verbal, visual, and working memory and executive functioning, functions commonly found to be mildly impaired in mTBI and PTSD. The two groups were compared on trajectories of change over time using linear mixed-effects models with restricted maximum likelihood (LMM). Contrary to our hypothesis that SMART would result in superior improvements compared to BHW, both groups displayed statistically and clinically significant improvements on measures of memory, executive functioning, and gist reasoning. Over 60% of the sample showed clinically significant improvements, indicating that gains can be found through psychoeducation alone. A longer SMART protocol may be warranted for clinical samples in order to observe gains over the comparison group.